CFD Modeling of Legionella's Atmospheric Dispersion in the Explosive Outbreak in Murcia, Spain. Issue 11 (13th August 2017) - Consuegro, Antonio J.; Kaiser, Antonio S.; Zamora, Blas; Viedma, Antonio; Sánchez, Francisco; Hernández, Mónica; Lucas, Manuel; Ruiz, Javier
ABSTRACT: Cooling towers, among other equipment, could have an important atmospheric impact, becoming a source of pollutants or biological agents. The most important, due to its frequency and importance of the outbreaks, is Legionella. Since its discovery in 1976 in Philadelphia, PA, several outbreaks have been reported causing tens of deaths. The most important one took place in the city of Murcia, Spain, in 2001, with more than 600 cases. In the present work, a validated numerical model using the computational fluid dynamics code ANSYS Fluent is employed to simulate the dispersion of the drift from the cooling tower causative of the outbreak in the urban environment of Murcia in the days of highest emissions. The results of the model are compared with the results of the epidemiological investigation carried out by the Epidemiology Service (Consejería de Sanidad, Murcia, Spain). The main objective of this model is to predict a cooling tower influence area, and what will help to reduce environmental and personal impact in case of an infection of its water or to improve the resources used to find the focus of infection after an outbreak has taken place. The model was previously validated using data from an experimental cooling tower installation.